ASUHAN KEPERAWATAN PADA AN.M DENGAN DEMAM TIFOID: SEBUAH STUDI KASUS - oktaviani saputri (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2020)
Typhoid fever is a disease that often occurs in tropical countries like Indonesia. In Indonesia it is estimated that there are as many as 300-810 cases per 100.000 population each year with the most sufferers in the 2-15 years age group. Typhoid fever is an acute infections disease that occurs in the digestive tract or small intestine caused by the bacterium Salmonella Typhii which is characterized by high fever or hyperthermia in the late afternoon. If hyperthermia is not treated immediately it can cause febrile seizures, shock, until death. The purpose of this research is to provide nursing care for typhoid fever children in Pasar Minggu Hospital. This research method uses a case study conducted on 25-28 February 2020 at Pasar Minggu Hospital using participants of a girl aged 1 year 3 months with medical diagnosis of typhoid fever, GES sign of dehydration, and ARI. Data collection is done by interview, observation, and physical examination. Results from the study of the client’s body temperature from the beginning of hospital admission were 37.80C. After the nursing action is taken the client’s body temperature is 37.10C. This condition is in accordance with the expected outcomes after 3 days of nursing care. Based on these results it is expected that the client’s mother can pay attention to the client’s health by maintaining personal hygiene and the environment, and must always pay attention to the food to be eaten and culture to wash hands before and after eating to avoid bacteria that will enter the body.